1992
DOI: 10.1254/jjp.59.43
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Intravenous Taurine Infusion on Electroretinographic Disorder in Taurine Deficient Rats

Abstract: ABSTRACT-We investigated the effect of intravenous taurine infusion on the electroretinogram (ERG) of taurine-deficient rats produced by treatment with guanidinoethyl sulfonate (GES), a taurine transport inhibitor. Mother rats were fed a taurine-free diet and given drinking water containing 1% GES from 2 weeks of gestation to weaning. The same feeding conditions were applied to male offspring after weaning. Both ERG measurement and continuous infusion of taurine at a dose of 10, 30 or 100 mg/animal/day were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…11 Decreased amplitudes and increased implicit times of b-and/or a-wave in the Ganzfeld-electroretinography (ERG) of taurine depleted rats have already been reported. 12,13 In tissue culture and bioassay experiments a significant improvement of the microcellular integrity and the cell survival rate as well as a neuroprotective effect under ischemia could be shown. 14 It has been suggested that the retinal damage following exposition to light (as for instance under the operating microscope) is probably associated with the release of taurine from the retina through the retinal pigment epithelium into the choroids.…”
mentioning
confidence: 99%
“…11 Decreased amplitudes and increased implicit times of b-and/or a-wave in the Ganzfeld-electroretinography (ERG) of taurine depleted rats have already been reported. 12,13 In tissue culture and bioassay experiments a significant improvement of the microcellular integrity and the cell survival rate as well as a neuroprotective effect under ischemia could be shown. 14 It has been suggested that the retinal damage following exposition to light (as for instance under the operating microscope) is probably associated with the release of taurine from the retina through the retinal pigment epithelium into the choroids.…”
mentioning
confidence: 99%
“…In the retina, decreased taurine uptake was also found to induce retinal degeneration indicated by disorganization of the outer nuclear layer (ONL) with photoreceptor damage and eventually cell death (Hayes et al 1975; Schmidt et al 1976; Anderson et al 1979; Barnett and Burger 1980; Lake and Malik 1987; Imaki et al 1993, 1998; Leon et al 1995). In some of these studies, some retinal dysfunction was also evidenced by eletroretinogram measurements (Jacobson et al 1987; Quesada et al 1988; Shimada et al 1992). …”
Section: Introductionmentioning
confidence: 99%